Assessment of livelihood wellbeing and empowerment of hill women through Farmers Producer Organization: A case of women based Producer Company in Uttarakhand - mukherjee, Anirban; singh, premlata; satyapriya, satyapriya; rakshit, shantanu; burman, rajarshi roy; shubha, kumari; kumar, shiv (The Indian Journal of Agricultural Sciences, 2020)
Hill agriculture is different from agriculture at plains, in respect to land type, altitude and climate, in addition to lack of infrastructure and fragmented land holding. Due to lack of employment opportunities hill farmers are leaving agriculture and migrating to plains. Lack of industries and marketing infrastructure has made it more difficult for farmers to excel in farm business. Farmers Producer Company (FPC) has emerged as a new agri-business model and is working in hilly areas it too. With an intention to find out the effectiveness of hill based FPC for enhancing livelihood wellbeing and empowering women farmers in hills the present study was conducted by selecting an women farmer based Organization, Mahila Umang Producer Company (MUPC) of a group of hill rural women. An ex-post facto research design was used. Difference in difference research design was used to calculate the actual impact of FPC. To measure the livelihood wellbeing an index were prepared by following the standard protocol. The study was conducted in Almora district of Uttarakhand from 37 randomly selected members of MUPC and 20 nonmember respondents from the same locale. The MUPC was found effective in enhancing income and empowering hill women. Joining the FPC has improved the hill women’s livelihood in terms of economic, human, and political dimensions.